2005
DOI: 10.1126/science.1106028
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Diversity Within a Natural Coastal Bacterioplankton Population

Abstract: The genomic diversity and relative importance of distinct genotypes within natural bacterial populations have remained largely unknown. Here, we analyze the diversity and annual dynamics of a group of coastal bacterioplankton (greater than 99% 16 S ribosomal RNA identity to Vibrio splendidus ). We show that this group consists of at least a thousand distinct genotypes, each occurring at extremely low environmental concentrations (on average less than one cell per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
294
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 337 publications
(318 citation statements)
references
References 30 publications
20
294
2
2
Order By: Relevance
“…Only a few studies have revealed the microdiversity of free-living bacterial populations (1,29,42,45). The investigated PnecC population differed from these populations in a low microdiversity and a strongly uneven population structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only a few studies have revealed the microdiversity of free-living bacterial populations (1,29,42,45). The investigated PnecC population differed from these populations in a low microdiversity and a strongly uneven population structure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Acinas et al (1) demonstrated by the construction and analysis of 16S rRNA clone libraries that a coastal bacterioplankton community contained a very high diversity of ribotypes, the vast majority of which fell into phylogenetically microdiverse sequence clusters (Ͻ1% divergent 16S rRNA sequences). Similarly, extensive microdiversities were also observed in populations of sulfate-reducing bacteria inhabiting a salt marsh (29) and in a Vibrio splendidus population from coastal bacterioplankton (42). The V. splendidus population consisted of at least a thousand distinct genotypes, which demonstrated a high variability in genome size and allelic composition (42).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Previous studies have detected variation in species composition in various habitats, both spatially (reviewed, for example, in Refs [35,[63][64][65]) and temporally (for example, Refs [66,67]). Spatio-temporal variation has been linked to variation in environmental conditions [35,68], even to the point at which environmental parameters can be predictive of species composition [55].…”
Section: Spatial and Temporal Variationmentioning
confidence: 99%